2020
DOI: 10.1111/camh.12367
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent mental health trajectories in relation to exclusion from school from the Avon Longitudinal Study of Parents and Children

Abstract: Background: As the prevalence of childhood mental health conditions varies by age and gender, we explored whether there were similar variations in the relationship between psychopathology and exclusion from school in a prospective UK population-based birth cohort. Method: The Avon Longitudinal Study of Parents and Children collected reports of exclusion at 8 years and 16 years. Mental health was assessed at repeated time points using the Strengths and Difficulties Questionnaire (SDQ). Results: Using adjusted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
(41 reference statements)
3
27
0
Order By: Relevance
“…Our data demonstrated that feelings of loneliness and trouble sleeping due to worries were associated with hunger owing to not having enough food at home. Poverty, low salary, and lack of access to services predispose an individual to dissatisfaction and lower quality of life, and consequently, to a greater likelihood of developing psychiatric disorders and adopting risky behaviors [ 10 , 38 ]. Aside from the socioeconomic impacts, food insecurity is also related to poor sleep quality, which may justify trouble sleeping due to worries [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that feelings of loneliness and trouble sleeping due to worries were associated with hunger owing to not having enough food at home. Poverty, low salary, and lack of access to services predispose an individual to dissatisfaction and lower quality of life, and consequently, to a greater likelihood of developing psychiatric disorders and adopting risky behaviors [ 10 , 38 ]. Aside from the socioeconomic impacts, food insecurity is also related to poor sleep quality, which may justify trouble sleeping due to worries [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research around the world has shown mixed results when it comes to gender and mental health during childhood and adolescence, depending on the mental health indicators researched. In general, a large body of research consistently points to gender differences when it comes to adolescent mental health, to the detriment of girls (Tejerina-Arreal et al 2020;Berg et al 2017;UNICEF 2017;WHO 2014b). In a large study conducted by UNICEF in 31 European countries, twice as many girls reported symptoms related to their mental health as boys at ages 13 and 15 (UNICEF 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An example being discussing climate change with reference to the impact of food choices (as this is something that is done every day), or using a natural hazard that captured the public's attention to introduce plate tectonic processes (e.g., Iceland's Eyjafjallajökul volcanic eruption of 2010 or Hunga-Tonga eruption and tsunami of 2022). Many learners will continue to be excluded from learning opportunities in any classroom setting that doesn't take into consideration these accessibility issues, impacting not only their educational and professional progress but also their mental wealth and wellbeing (Tejerina-Arreal et al, 2020).…”
Section: Accessiblementioning
confidence: 99%